Crystalline polysaccharides: A review - Seidi, Farzad; Yazdi, Mohsen Khodadadi; Jouyandeh, Maryam; Habibzadeh, Sajjad; Munir, Muhammad Tajammal; Vahabi, Henri; Bagheri, Babak; Rabiee, Navid; Zarrintaj, Payam; Saeb, Mohammad Reza (Carbohydrate polymers, 2022)
The biodegradability and mechanical properties of polysaccharides are dependent on their architecture (linear or branched) as well as their crystallinity (size of crystals and crystallinity percent). The amount of crystalline zones in the polysaccharide significantly governs their ultimate properties and applications (from packaging to biomedicine). Although synthesis, characterization, and properties of polysaccharides have been the subject of several review papers, the effects of crystallization kinetics and crystalline domains on the properties and application have not been comprehensively addressed. This review places focus on different aspects of crystallization of polysaccharides as well as applications of crystalline polysaccharides. Crystallization of cellulose, chitin, chitosan, and starch, as the main members of this family, were discussed. Then, application of the aforementioned crystalline polysaccharides and nano-polysaccharides as well as their physical and chemical interactions were overviewed. This review attempts to provide a complete picture of crystallization-property relationship in polysaccharides. •Crystallization of polysaccharides was reviewed and discussed.•Properties and applications of crystalline polysaccharides are reviewed and discussed.•Effects of crystallinity of polysaccharides on their properties were evaluated.•Physical and chemical modifications of polysaccharides are classified.•Nanostructured polysaccharides and their crystallization were reviewed.